Tacit collusion in the presence of cyclical demand and endogenous capacity levels - Christopher R. Knittel; Jason Lepore (University of California, Department of Economics, 2006)
We analyze tacit collusion in an industry characterized by cyclical demand and long-run scale decisions; rms face deterministic demand cycles and choose capacity levels prior to competing in prices. Our focus is on the nature of prices. We nd that two types of price wars may exist. In one, collusion can involve periods of mixed strategy price wars. In the other, consistent with the Rotemberg and Saloner (1986) denition of price wars, we show that collusive prices can also become countercyclical. We also establish pricing patterns with respect to the relative prices in booms and recessions. If the marginal cost of capacity is high enough, holding current demand constant, prices in the boom will be generally lower than the prices in the recession; this reverses the results of Haltiwanger and Harrington (1991). In contrast, if the marginal cost of capacity is low enough, then prices in the boom will be generally higher than the prices in the recession. For costs in an intermediate range, numerical examples are calculated to show specifc pricing patterns.
Keywords: 330